COVID-19 Lockdown: A Fertile Ground for Gender-Based Violence in South Africa - Netshitangani, Tshilidzi (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Gender-based violence (GBV) has always been an issue of concern in South Africa and Globally. This problem of gender-based violence is currently exacerbated due to the lockdown restrictions. Women and children are targets for Covid-19 related frustrations as gender-based violence reports increase during the lockdown period. Across the country, civil society groups, gender-based violence advocacy organisations, religious groups, and other social justice groups have reported an increase in incidences related to violence against women and children and heightened demand for emergency shelters. Moreover, at the beginning of June 2020, Nehawu mentioned that reports suggested that the number of gender-based violence cases had risen by 500 per cent since the start of the Covid-19 lockdown. Employing the literature review, the paper elaborates on the nature of gender-based violence reported in South Africa and further highlights how gender-based violence has increased during the lockdown period. In this paper, I use the social dominance theory to understand the escalation of gender-based violence when people ought to be focusing on curbing the spread of the COVID-19 pandemic. Observing COVID-19 protocols and encouraging one another to adhere to protocols in the endeavour to reduce the spread of the pandemic ought to be the focus of everyone irrespective of their gender. The suggestions on how to eliminate the scourge of gender-based violence with the advent of the COVID-19 are herein presented.